PERAN DINAS PARIWISATA DAN KEBUDAYAAN (DISPARBUD) DALAM PENINGKATAN PAD KABUPATEN PANDEGLANG (STUDI PADA OBYEK WISATA PANTAI CISIIH/PARTA BEACH KECAMATAN CIMANGGU KABUPATEN PANDEGLANG) - Sofian, Mochamad Yordan; Wahyiah, Ita Rosita; Arifin, Suherman; Endayani, Endayani; Fatoni, Malik (Gapenas Publisher, 2025)
This study aims to examine the role of the Department of Tourism and Culture (Disparbud) of Pandeglang Regency in increasing local revenue (PAD) through the management of the tourism object at Cisiih Beach (Parta Beach) in Cimanggu District. This research employs a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The study adopts the tourism management theory proposed by Andi Mappi Sammeng (2000), which includes three main aspects: development, institutionalization, and regulation. The findings reveal that the role of Disparbud in managing Cisiih Beach has not been optimal. Several obstacles were identified, including the lack of infrastructure, limited digital promotion, and low community involvement. Nevertheless, the tourism office has made several efforts such as internal promotions, coordination with local businesses, and environmental education for local residents. It is recommended that stronger synergy between the local government, community, and private sector be established. Additionally, the formulation of technical regulations and structured community empowerment programs are needed to ensure sustainable tourism management and contribute to the growth of local revenue in Pandeglang Regency.